Ethical Behavior, Work Values and Performance of the Provincial Government Officers of Agusan, del Sur, Philippines, in the light of ASEAN Integration - JED P. ACERO (Universitas Muhammadiyah Yogyakarta, 2016)
This descriptive-correlation determined the level of ethical behavior, work valuesand performance of the Provincial Government Officers of Agusan del Sur, Philippines. Findings served as the bases for intervention scheme through an orientation plan for the recommended programs. There is a very high level of ethical behavior, high level of work values and excellent performance of PGAS’ department heads. There is no significant relationship between the subjects’ profile and their level of ethical behavior. There is no significant relationship between respondents’ profile and their level of work performance. However, there is a significant relationship between respondents’ level of ethical behavior and work values. There is a significant difference between the level of ethical behavior as perceived by the different respondents: municipal mayors, department heads,and its employees. However, there is no significant difference between the levelsof work values as perceived by the different research-respondents and no significant difference between the levels of work performance as perceived by theresearch-respondents. There is a difference on the actual rating and perceivedwork performance of the rating of the respondents. The proposed interventionscheme through and orientation plan as programs for PGAS’ department headsafter thorough study shall be implemented, monitored and evaluated by boththe PGAS’ department heads, non-government organizations and other stakeholders.